Mechanical thrombectomy for reperfusion of acute ischemic stroke in a Stroke Unit in Argentina - Matías ALET; Federico Rodríguez LUCCI; Sebastián AMERISO (Arquivos de Neuro-Psiquiatria)
Abstract Stroke is an important cause of morbidity and mortality worldwide. Reperfusion therapy with intravenous tissue plasminogen activator (IV-tPA) was first implemented in 1996. More recently, endovascular reperfusion with mechanical thrombectomy (MT) demonstrated a robust beneficial effect, extending the 4.5 h time window. In our country, there are difficulties to achieve the implementation of both procedures. Objective: Our purpose is to report the early experience of a Comprehensive Stroke Center in the use of MT for acute stroke. Methods: Analysis of consecutive patients from January 2015 to September 2018, who received reperfusion treatment with MT. Demographic data, treatment times, previous use of IV-tPA, site of obstruction, recanalization, outcomes and disability after stroke were assessed. Results: We admitted 891 patients with acute ischemic stroke during this period. Ninety-seven received IV-tPA (11%) and 27 were treated with MT (3%). In the MT group, mean age was 66.0±14.5 years. Median NIHSS before MT was 20 (range:14‒24). The most prevalent etiology was cardioembolic stroke (52%). Prior to MT, 16 of 27 patients (59%) received IV-tPA. Previous tPA treatment did not affect onset to recanalization time or door-to-puncture time. For MT, door-to-puncture time was 104±50 minutes and onset to recanalization was 289±153 minutes. Successful recanalization (mTICI grade 2b/3) was achieved in 21 patients (78%). At three-month follow-up, the median NIHSS was 5 (range:4‒15) and mRS was 0‒2 in 37%, and ≥3 in 63%. Conclusions: With adequate logistics and strict selection criteria, MT can be implemented in our population with results like those reported in large clinical trials.